(3GdgOGjI TQM GdHOGjIs - (3GdnerQpZjfGfj GdaQZGfj, CHh GdMSf, HQgGf GdOjf, Ydj Hf CHj HcQ Hf YHO GdLdjd, (B593 (3g`s ((3eMeO GdgTjej GdMfaj Hf ehdGfG LGQ Gddg Hf ceGd GdOjfs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj CYdi eYGde GdYde hCYdGeg hbO LQi Ydi GdhYO aj eHOC HOGjI GdeHJOj Cf CTQMgG aUQaJ hGdYfGf hGdYfGjI Edi TQM ehShe HGdgOGjI CLeY ajg HJhajb Gddg Hjf Yjhf GdQhGjI heJhf GdOQGjI s
(3BNQgG (B:s
(3aEf Cgd GdYQa jQjOhf HPdc aj GdZdI GdabQGA hZjQgG GdJShjI Hjfge hHjf GdCZfjGA hdCf GdMGLI JTed GdZfj hGdabjQ aj GdfRhd hGdTQH hGdZfi dG jMJGL Edi UQa gPg GdZdI dZfGgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 266s
(3eYLe GdeDdajf (B2 / 411s
(3cTa GdXfhf (B2 / 2031s
(3gOjI GdYGQajf (B1 / 702s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs